Carpe diem or carpe mañana? Emotion priming affects intertemporal choice among Internet addicts and normal Internet users - Li, Hongxia; Shan, Wen (Frontiers in Psychology, 2022)
In this digitalized era, Internet addiction has been a severe problem that needs imperative solutions derived from the same mechanism that leads to its addiction. To uncover a more nuanced mechanism for Internet addiction in association with decision-making focus and emotions and thus generate effective interventions, we conducted three experiments to investigate how various forms of emotion priming affect intertemporal choice among Internet addicts and normal Internet users. We divided the emotions into three categories, namely emotional valence (negative and positive emotions), expected emotion type (expected regret, expected joy), and current emotion type (current regret, current joy). In experiment one, we examined the effect of two participant types (Internet addicts and normal Internet users) with three emotion valences (positive, negative, and neutral). In experiment two, we examined the effect of two participant types (Internet addicts and normal Internet users) with three current emotion types (current regret, joy, and neutral). In experiment three, we examined the effect of two participant types (Internet addicts and normal Internet users) with two expected emotion types (expected regret and expected joy). We conducted a completely randomized experimental design in each experiment and used subjective value as the dependent variable index of intertemporal choice. The results showed that the subjective value of Internet addicts was significantly lower than that of normal Internet users across three studies. The subjective value of individuals primed with positive emotions was significantly higher than those primed with negative emotions, no matter whether they were normal Internet users or addicts (experiment one). The subjective value of individuals primed with expected joy was significantly higher than those primed with expected regret, no matter whether they were normal Internet users or addicts (experiment three). When primed with current joy, however, the Internet addicts' subjective value was significantly lower than when primed with current regret, but this did not apply to normal Internet users (experiment two). These results suggest positive emotions and expected joy enhanced long-term goals and greater rewards focus on intertemporal decision-making compared to negative emotions and expected regret. However, current joy facilitated short-term goals, and smaller rewards focus on intertemporal decision-making compared to current regret. The theoretical and practical implications for Internet addiction are also discussed in this paper.